1983
DOI: 10.2170/jjphysiol.33.827
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline-induced secretions of pancreatic hormones in cold- and heat-acclimated rats.

Abstract: Effects of noradrenaline on the portal and aortic plasma pancreatic hormone concentrations were studied in the cold-and heatacclimated rats in order to know possible roles of these hormones in temperature acclimation. Noradrenaline (NA) infusion (2 ,ug/min, i.v., 30 min) effected greater elevation of colonic temperature (Ta) in the cold-acclimated rats (CA) than in the warm controls (WC), and did not influence T~ in the heat-acclimated rats (HA) under hexobarbital anesthesia. Portal and aortic glucagon levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The present result clearly indicated that cold acclimation causes a potentiation in glucagon-secreting action of noradrenaline, confirming the previous study that NA infusion elevated plasma glucagon in portal vein and abdominal aorta of coldacclimated rats under anesthesia (KUROSHIMA et al, 1983). In the latter experiment, however, NA infusion did not affect the glucagon levels in WC in contrast to the significant increases in the present result.…”
Section: Discussionsupporting
confidence: 91%
“…The present result clearly indicated that cold acclimation causes a potentiation in glucagon-secreting action of noradrenaline, confirming the previous study that NA infusion elevated plasma glucagon in portal vein and abdominal aorta of coldacclimated rats under anesthesia (KUROSHIMA et al, 1983). In the latter experiment, however, NA infusion did not affect the glucagon levels in WC in contrast to the significant increases in the present result.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, the rapid increase in body temperature associated with increased thermogenesis due to exercise training is similar to a state of intermittent mild heat exposure. As heat exposure has been reported to have an inhibitory effect on norepinephrine (NE)-dependent non-shivering thermogenesis (NST) [ 42 ], it is possible that the increase in body temperature due to strength training also inhibited the increase in BAT-d in this study. As BAT is essentially an adaptive thermogenic tissue in cold environments, the attenuated increase in BAT-d as a whole in this study might be a reasonable outcome.…”
Section: Discussionmentioning
confidence: 89%
“…In agreement with these reports, the present experiments further confirmed that the increased amylase activity was correlated well with the higher plasma insulin concentration due to heat exposure. It was reported in a previous study that the plasma insulin and glucose concentrations were low in non-starved, heat-exposed rats Kuroshima, Habara & Ohno, 1983). Accordingly, the present experiment had been first designed to expect suppression of amylase release due to the decreased insulin concentration.…”
Section: Discussionmentioning
confidence: 98%